The Pengaruh Model Pendampingan Terhadap Kepatuhan Pengobatan Pasien Tuberkulosis Resisten Obat (TB RO) - Sri Arini WInarti Rinawati; Bondan Palestin; Yopi Harwinanda Ardesa (NHM PRESS, 2022)
Background: Drug resistant Tuberculosis (TB RO) patients need external support from others in the form of patient assistance in order to realize quality and patient-centered TB services. Objective: Knowing the results of the influence of the mentoring model on TB RO patients in DIY. Method: Is a quasi-experimental study of 30 RO TB patients in the Special Region of Yogyakarta, with the aim of knowing the level of knowledge and demographic characteristics of RO TB patients. This research has been declared ethically feasible based on KEPK Number e-KEPK / POLKESYO / 0619 / VIII / 2022. Result: TB RO patients are mostly ≥ 45 years old with male gender. There was a relationship between knowledge of adherence to RO TB treatment as evidenced by pearson tests showing significant results between the two variables, with a p value = 0.000 (<0.01). The mentoring model carried out has a significant influence on adherence to RO TB treatment. As evidenced by the results of mann Whitney's test and analysis, there is a value of 0.037 (<0.05). Conclusion: Knowledge provides a significant impact on adherence to RO TB treatment. Keywords : Influence, Obedience, Drug-resistant Tuberculosis